2022
DOI: 10.13075/ijomeh.1896.01854
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick and sharps injuries at a German university hospital: epidemiology, causes and preventive potential – a descriptive analysis

Abstract: To analyze the number, epidemiology and circumstances of needlestick and sharps injuries (NSSI) and exposures to body fluids and to identify further preventive measures to improve the occupational safety of health care workers (HCW). Material and Methods: Setting: German university tertiary-care referral center. Retrospective study based on injury documentation sheets of the hospital's staff and faculty health service and, if given, on reports by continuity doctors and by the accident and emergency department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Nevertheless, exposures of HCW to potentially infectious body material occur. A single-center retrospective study with a large sample size found nearly 16% of cases of nonpreventable occupational exposures [ 1 ], which was similar to another study [ 18 ]. The incidence of occupational exposures such as needlestick injuries among HCW in this study was 13.3%, indicating that the current status of occupational exposures among HCW still cannot be ignored.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Nevertheless, exposures of HCW to potentially infectious body material occur. A single-center retrospective study with a large sample size found nearly 16% of cases of nonpreventable occupational exposures [ 1 ], which was similar to another study [ 18 ]. The incidence of occupational exposures such as needlestick injuries among HCW in this study was 13.3%, indicating that the current status of occupational exposures among HCW still cannot be ignored.…”
Section: Discussionsupporting
confidence: 76%
“…Needlestick and sharps injuries are skin injuries caused by objects contaminated with potentially contagious material [ 1 ]. In addition, skin and mucous membranes can be exposed to potentially infectious body fluids through splashes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioactive laboratories present special safety challenges due to the presence of radioactive sources, isotopes, and devices that emit invisible but highly lethal radiation in the form of α (alpha) particles, β (beta) particles, and γ (gamma) rays. , Exposure to these rays can cause various degrees of radiation biological impacts, leading to specific injuries and potential hazards, such as radiation-induced cancer and genetic effects. , As a result, additional safety precautions beyond those used in regular chemical laboratories are required to prevent long-term harm to humans and the environment.…”
Section: Radiological Hazards In a Radiochemistry Laboratorymentioning
confidence: 99%
“…Based on research conducted by occupational health departments in different geographical areas around the world, several potential risk factors have been identified for a healthcare provider to suffer a biohazard accident [ 11 , 12 , 13 ] or to perform an incorrect notification for that matter [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%